Analysis of image heterogeneity using 2D Minkowski functionals detects tumor responses to treatment. Issue 1 (25th February 2013) - Larkin, Timothy J.; Canuto, Holly C.; Kettunen, Mikko I.; Booth, Thomas C.; Hu, De‐En; Krishnan, Anant S.; Bohndiek, Sarah E.; Neves, André A.; McLachlan, Charles; Hobson, Michael P.; Brindle, Kevin M.
<x xml:space="preserve">Abstract</x> Purpose The acquisition of ever increasing volumes of high resolution magnetic resonance imaging (MRI) data has created an urgent need to develop automated and objective image analysis algorithms that can assist in determining tumor margins, diagnosing tumor stage, and detecting treatment response. Methods We have shown previously that Minkowski functionals, which are precise morphological and structural descriptors of image heterogeneity, can be used to enhance the detection, in T1‐weighted images, of a targeted Gd3+‐chelate‐based contrast agent for detecting tumor cell death. We have used Minkowski functionals here to characterize heterogeneity in T2‐weighted images acquired before and after drug treatment, and obtained without contrast agent administration. Results We show that Minkowski functionals can be used to characterize the changes in image heterogeneity that accompany treatment of tumors with a vascular disrupting agent, combretastatin A4‐phosphate, and with a cytotoxic drug, etoposide. Conclusions Parameterizing changes in the heterogeneity of T2‐weighted images can be used to detect early responses of tumors to drug treatment, even when there is no change in tumor size. The approach provides a quantitative and therefore objective assessment of treatment response that could be used with other types of MR image and also with other imaging modalities. Magn Reson Med 71:402–410, 2014. © 2013 Wiley Periodicals, Inc.